Incorporating Active Learning into Moral Education to Develop Multiple Intelligences: A Qualitative Approach - Nadarajan Thambu; Harun Joko Prayitno; Gamal Abdul Nasir Zakaria (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
Recognizing and nurturing all the varieties of human intelligences is essential for exploring the talents of students and enabling their identification of multiple intelligences. Studies have suggested that eliciting the maximum potential of intelligences leads to students' success in their academic and future careers. The literature has shown that incorporating active learning into the teaching and learning of moral education to develop multiple intelligences is limited. Accordingly, this study aims to discover the various intelligences that exist among moral education students through the active learning method. Active learning implies that all learners are provided with time and assistance to realize their potential. In this regard, multiple intelligence theory is used as the theoretical framework for defining, understanding, developing, and estimating the various intelligences that students have. The research design for this study is the qualitative method. A total of fourteen students from two schools were chosen as research participants. Data were collected through observation, focus group interviews, and journal entries. These findings reveal that using the active learning method in moral education can develop students’verbal linguistic intelligence, logical–mathematical intelligence, musical intelligence, spatial intelligence, bodily kinesthetic intelligence, intrapersonal intelligence, interpersonal intelligence, and naturalistic intelligence. Integration and internalization of the eight intelligences into active learning holistically will shape the personality and character of students in social life.